New Trends and Socio-Spatial Relations in Gated Communities - Levent Taş; Esra Burcu Sağlam (Journal of Economy Culture and Society, 2020)
This study focuses on the socio-spatial relationship constructed in gated communities. Great urban transformation has been observed in the urban life during the second half of the 20th century. Transformation in this period changed urban space as well as the daily life and social relationships of city dwellers. Gated communities are a sign of both spatial transformation and change within the social relationships in cities. The first gated communities appeared as living spaces serving as an isolation for the elite class from lower classes of society and problems of the city. Research conducted on gated communities were often related to such issues as socio-spatial segregation. However, by building gated communities for the middle class, these communities became more visible in the urban view and began to influence urban life and social relationships more. Hence, the social-spatial relationship constructed in gated communities became more significant in terms of urban life. This research was designed according to qualitative research methods and the data for research was acquired from in-depth interviews. The data showed that besides community and society type relationships, networking type relationships, and fluid social relationship were constructed in gated communities. Based on the data, it was concluded that discussing relationships constructed in gated communities was insufficient within the frame of the community-society type relationships constructed in these communities and new research is needed on this subject.